Uji Organoleptik Ikan Beku Pada Kmn. Naili XX Yang Berpangkalan Di PPS Nizam Zachman Jakarta Utara - Rasdam Rasdam; Resky Amalia Rajab; Irandha C.M Siahaan; Paulus Miki Tuen (Jurnal Akuatik, 2022)
Fish must be given a good treatment or handling so that the quality and quality does not decrease, the application of a principle of handling quickly, carefully, cleanly, healthy and low temperature application. The purpose of this study was to describe the organoleptic test results of frozen fish at KM Naili-XX, which is based at the Nizam Zachman Ocean Fishing Port, North Jakarta. This research was carried out from November 2020 to May 2021. Organoleptic tests were carried out following the procedures in SNI 01-2346-2006 regarding Instructions for Organoleptic and/or Sensory Tests. The results showed that based on the results of organoleptic testing at the time of loading I with an average value of 7.88 at the time of loading II the average value was 7.77 and at the time of unloading the average value was 7.66, meaning that it met the fish classification standard. frozen (SNI 4110-2014), namely products fit for consumption or for export. Keywords: Collecting Vessel, Organoleptic Test, Frozen Fish